Simulation of the behavior of reinforced concrete rectangular hollow sandwich plates under the effect of contact explosion through SPH method - Bakir, Dursun; Savas, Sedat; Üstündağ, Hasan (Revista de la Construcción. Journal of Construction, 2024)
When dealing with contact explosion, a type of explosion load that has a substantial impact on structures, it is necessary to use a distinct approach compared to other types of explosion loads. Hence, utmost significance should be attributed to the selection of the analytical approach when modeling the explosion. It is crucial to ascertain the behavior of the explosion pressure in the space between hollow sandwich plates. This work involved conducting experiments to examine the accurate simulation of hollow plates subjected to contact explosions, which result in a reduction in the dispersion of explosive pressure. The structure was modeled using smooth particle hydrodynamics (SPH) and Lagrangian modeling techniques, taking into account the effects of explosives and contact explosions. The mesh-free structure of these approaches makes them highly successful in resolving significant deformations resulting from explosions. The comparison criteria included the widths of the crater pits on the upper surface of the plate, the behavior of the explosion pressure in the structure cavity, and the impact of the explosion load on the lower section of the plate. After evaluating several explosion load and hollow structure modeling methodologies, it was concluded that the most appropriate approach for reproducing the experimental results involved using Smoothed Particle Hydrodynamics (SPH) to model the explosive and Lagrangian method to model the structure.